1993
DOI: 10.4269/ajtmh.1993.48.365
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium Falciparum-Associated Anemia in Children at a Large Urban Hospital in Zaire

Abstract: Chloroquine-resistant Plasmodium falciparum malaria and human virus (HIV) infection through blood transfusions used to treat malaria-associated anemia are causes of increasing morbidity and mortality among children in Africa. To evaluate the role of malaria and other risk factors for pediatric anemia, we conducted a study of children brought to the emergency ward of a large urban hospital in Kinshasa, Zaire. A total of 748 children ages six through 59 months were enrolled; 318 (43%) children were anemic (hemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
1
2

Year Published

1994
1994
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 0 publications
2
45
1
2
Order By: Relevance
“…Forty-three percent of the children less than five years of age who were brought to the emergency ward of a hospital in Kinshasa, Zaire were anemic. 3 Moreover, in a three-year longitudinal survey with a half-year follow-up, our results specified the age-related decrease in the prevalence of anemia in children from six to 60 months of age. Our study clearly showed a decrease in the prevalence of anemia after 30 months of age (42% versus 21% before and after 30 months of age, respectively; P Ͻ 10 -8 ).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Forty-three percent of the children less than five years of age who were brought to the emergency ward of a hospital in Kinshasa, Zaire were anemic. 3 Moreover, in a three-year longitudinal survey with a half-year follow-up, our results specified the age-related decrease in the prevalence of anemia in children from six to 60 months of age. Our study clearly showed a decrease in the prevalence of anemia after 30 months of age (42% versus 21% before and after 30 months of age, respectively; P Ͻ 10 -8 ).…”
Section: Discussionmentioning
confidence: 82%
“…Several previous studies have demonstrated an association between anemia and symptomatic malaria. 3,4 Since most of the children in our study were asymptomatic, we suggest that asymptomatic malaria is also a strong risk factor for anemia in children. 16,[18][19][20][21][22] The frequency of parasitemia was not a significant risk factor in the multivariate model, suggesting that the mechanism responsible for malaria-related anemia involved predominantly acute hemolysis as compared with dyserythropoiesis or ineffective erythropoiesis due to recurrent parasitemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] The World Health Organization estimates that the prevalence of anemia, defined by a hemoglobin concentration of less than 11.0 g/dL in African children less than five years of age, is approximately 33%. 5 Individual studies have estimated the prevalence of anemia to be from 24% in western Africa to almost 80% in western Kenya.…”
Section: Introductionmentioning
confidence: 99%